2019
DOI: 10.1111/ina.12536
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative filter forensics with residential HVAC filters to assess indoor concentrations

Abstract: Analysis of the dust from heating, ventilation, and air conditioning (HVAC) filters is a promising long‐term sampling method to characterize airborne particle‐bound contaminants. This filter forensics (FF) approach provides valuable insights about differences between buildings, but does not allow for an estimation of indoor concentrations. In this investigation, FF is extended to quantitative filter forensics (QFF) by using measurements of the volume of air that passes through the filter and the filter efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
(151 reference statements)
1
13
6
Order By: Relevance
“…The majority of interest in microbiology of the built environment has focused on microbially-mediated building deterioration or detriment to occupant health from specific microorganisms of interest. Despite advances in awareness of the potential for microbial exposure indoors [33], microorganisms in the built environment are still considered as debris to be removed, instead of members of a microbial ecosystem which is inexorably linked to the influences of building inhabitants [29,31,[34][35][36][37]. Given the propensity for microbial biofilms or overgrowth to pose a threat to the health of occupants, it is not difficult to understand why.…”
Section: From Fear To Reluctant Acceptance Of the Microbial Worldmentioning
confidence: 99%
“…The majority of interest in microbiology of the built environment has focused on microbially-mediated building deterioration or detriment to occupant health from specific microorganisms of interest. Despite advances in awareness of the potential for microbial exposure indoors [33], microorganisms in the built environment are still considered as debris to be removed, instead of members of a microbial ecosystem which is inexorably linked to the influences of building inhabitants [29,31,[34][35][36][37]. Given the propensity for microbial biofilms or overgrowth to pose a threat to the health of occupants, it is not difficult to understand why.…”
Section: From Fear To Reluctant Acceptance Of the Microbial Worldmentioning
confidence: 99%
“…The quantitative filter forensics approach by Haaland and Siegel (2017) was used in this work (Table S2) to estimate the temporally and spatially integrated airborne concentration (C) of SARS-CoV-2 over the viral collection time period. The following parameters were used for the calculation: m was the mass of dust (g) collected in the HVAC filter, f was the concentration of SARS-CoV-2 (N2 gene copies/g) in the dust collected on the filter, η was the integrated particulate matter filtration efficiency of the MERV-4 filter, Q was the volumetric air flowrate (m 3 /h) through the filter (median for the summer season for the same geographical location, (Givehchi et al, 2019) and t was the runtime of the HVAC system (h) over the duration of the SARS-CoV-2 collection time -approximately one month-, median for the summer season for the same geographical location, (Givehchi et al, 2019). A few considerations that ought to be taken into account are: (1) our estimate does not account for the attenuation of the signal over time or the losses due to deposition, (2) it considers the estimate that approximately 5.5% of the viral signal is recovered through RNA extraction from the dust matrix (as estimated in this work via the spike and recovery tests for the surrogate BRSV virus), (3) the mass recovered by the participants was estimated to be 68% of that recoverable by trained researcher (based on previous experiments comparing researcher-collected samples to participant-collected samples), and (4) that approximately 27% of the accumulated dust can be recovered from the filter (Mahdavi and Siegel, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The fact that the SARS-CoV-2 virus can be recovered from HVAC filter dust is not too surprising given that previous research has demonstrated that filters from central HVAC systems can serve as long-term spatially integrated samplers of the indoor environment. The filter forensics approach has been used for the assessment of particle-bond contaminants that accumulate in the dust collected on HVAC filters (Bi et al, 2018; Givehchi et al, 2019; Maestre et al, 2018; Noris et al, 2011) including viruses (Goyal et al, 2011; Prussin et al, 2016). When this approach is combined with HVAC parameters such as flowrate through the filter and usage time, it is possible to quantitatively estimate the time-averaged indoor concentrations of the particle-bound contaminants (Givehchi et al, 2019; Haaland and Siegel, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filter forensics has several benefits over other conventional particle exploration techniques such as airborne sampling and settled dust collection. When used in a fully recirculating distribution system and combined with the HVAC metadata (e.g., filter efficiency, runtime, and airflow rate), filter forensics provides a quantitative time-and space-integrated estimate of indoor particle characteristics due to a long-term passing of indoor air from the entire conditioned space through the filter (Stanley et al 2008;Batterman et al 2010;Haaland and Siegel 2017;Givehchi et al 2019). Airborne sampling and settled dust are often not spatially and temporally representative of indoor particles.…”
Section: Introductionmentioning
confidence: 99%